ANALYZING THE FINANCIAL RATIOS OF PT ASPIRASI HIDUP INDONESIA TBK IN 2024 TO ASSESS FINANCIAL PERFORMANCE - Badmir; Riski Rahmawati; Risti Nazila; Ramziati Piqqa; Asnawi (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
This study aims to analyze the financial performance of PT Aspiration Life Indonesia Tbk (formerly PT Ace Hardware Indonesia Tbk ) using the financial ratio analysis method. The research employs a descriptive quantitative approach with secondary data obtained from the company's 2024 financial statements. The analysis focuses on four main financial ratio categories: liquidity, solvency, activity, and profitability. The findings indicate that the company maintains a very strong liquidity position, as reflected by a Current Ratio of 6.81 times and a Quick Ratio of 2.92 times. In terms of solvency, the Debt to Asset Ratio of 20.49% and the Debt to Equity Ratio of 25.78% demonstrate a sound capital structure and low financial risk. The profitability ratios show effective management efficiency, with a Gross Profit Margin of 48.73%, Net Profit Margin of 10.30%, Return on Assets of 10.80%, and Return on Equity of 13.58%. However, the activity ratios indicate a relatively low inventory turnover (1.30 times) and moderate asset utilization efficiency (Total Asset Turnover of 1.05 times). Overall, the company exhibits a stable and promising financial condition, although improvements in inventory management efficiency are necessary to further optimize operational performance.